NX ship modelilng for AHTS ships safety management - Berescu, C; Bocanete, P (Technium: Romanian Journal of Applied Sciences and Technology, 2022)
The field of AHTS vessels is constantly evolving and represents a huge potential for offshore development. Offshore structures need AHTS vessels - an acronym for Anchor Handling Tug Supply Vessel. The present paper will present the NX modelling in NX softwater for AHTS ships.